2008
DOI: 10.1142/s0217751x08040925
|View full text |Cite
|
Sign up to set email alerts
|

LARGE WINDING SECTOR OF AdS/CFT

Abstract: We study a family of classical strings on R × S 3 subspace of the AdS 5 × S 5 background that interpolates between pulsating strings and single-spike strings. They are obtained from the helical strings of hep-th/0609026 by interchanging worldsheet time and space coordinates, which maps rotating/spinning string states with large spins to oscillating states with large winding numbers. From a finite-gap perspective, this transformation is realised as an interchange of quasi-momentum and quasi-energy defined for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 62 publications
(195 reference statements)
1
46
0
Order By: Relevance
“…At first glance there is a rescaling of the coupling as λ → r 2 0 (1 +V φ (∞))λ. However, this is exactly the dispersion relation in the appendix of [45] with no rescaling. The way to see this is to realise that r 2 0 (1+V φ (∞)) sums the area of all the black regions on the LLM plane -this is a fixed quantity for all LLM geometries!…”
Section: Analytic String Limitsmentioning
confidence: 58%
See 1 more Smart Citation
“…At first glance there is a rescaling of the coupling as λ → r 2 0 (1 +V φ (∞))λ. However, this is exactly the dispersion relation in the appendix of [45] with no rescaling. The way to see this is to realise that r 2 0 (1+V φ (∞)) sums the area of all the black regions on the LLM plane -this is a fixed quantity for all LLM geometries!…”
Section: Analytic String Limitsmentioning
confidence: 58%
“…It is for this reason that we would like to study the SL(2) sector of nonplanar N = 4 SYM on an LLM geometry. Our primary focus is on the string theory side of the correspondence, where we may compare with several works in the planar limit such as [40][41][42][43][44][45] and see if the rescaled coupling proposal of [21] is manifest in the spectrum of strings dual to localised operators. We hope furthermore to gain some insight into how the subsectors may be isolated on the string theory side.…”
Section: Introductionmentioning
confidence: 99%
“…7 The direct analogs of giant magnons for the AF ground state are single spikes (SSs) [23,24]. These are the string theory duals of N = 4 SYM (single) spinon states [25],…”
Section: Introductionmentioning
confidence: 99%
“…Like giant magnons, single spikes also belong to the class of long strings/strongly coupled operators for which there are no advanced spectroscopic tools at our disposal. Single spikes can be transformed to giant magnons by means of the τ ↔ σ transform or "2D duality" [25]:…”
Section: Introductionmentioning
confidence: 99%
“…Further, it was observed that N = 4 SYM in planar limit can be described by an integrable spin chain model where the anomalous dimension of the gauge invariant operators were found in [6], [7], [8], [9], [10], [11], [12]. In the dual picture, it was noticed that the string theory is integrable in the semiclassical limit as well, see for example [13], [14], [15], [16], [17], hence providing further insight into the AdS/CFT duality. However apart from few 'solvable' examples of AdS/CFT, in many cases the exact nature of the boundary operators is not known, and hence it is interesting to make calculations in the gravity side and then look for possible operators on the boundary by invoking the duality map.…”
Section: Introductionmentioning
confidence: 99%